Using sectional blasting to improve the efficiency of making cut cavities in underground mine workings - Lozynskyi, Vasyl; Yussupov, Khalidilla; Rysbekov, Kanay; Rustemov, Serikbay; Bazaluk, Oleg (Frontiers in Earth Science, 2024)
Introduction: The research concerns how making cut cavities improves drilling and blasting operations as well as the optimum parameters to arrange both snubber and auxiliary blastholes. Methods: The research methods include experimental and industrial activities to identify the optimum depth of the first-section snubber blastholes relative to the second-section blastholes. It also identifies optimum parameters of the snubber blastholes while driving mine workings and ore breaking in stopes with different mine working sections and different rock mass strengths broken using the technique of cut-cavity formation. Results and Discussion: Experimental explosions executed in a production environment have proved the efficiency of the proposed technique of sectional formation of a cut cavity, which helped increase the blasthole use coefficient (BUC) from 0.88 to 0.97. The depth of the first-section boreholes should be determined relative to the length of the second-section boreholes and the broken rock mass strength. The higher the strength of the broken formation, the larger the ratio between the first and the second-section blasthole lengths should be. The results of the experimental explosions indicate that the depth of first-section snubber blastholes varies from 0.5 and more of the second-section boreholes, depending upon the depth of the latter and the broken rock mass strength. If the strength of the broken rock mass is 12 on the Protodyakonov scale, and the second-section blasthole depth increases from 1.6 m to 2.6 m, then the depth of the second-section boreholes should be increased from 0.9 m to 1.54 m so as to be 0.55–0.56 of the second section blasthole length. If the strength of the broken rock mass is 18, and the length of the second section increases from 1.8 m to 2.82 m, then the first-section length varies from 0.9 m to 1.75 m, being 0.5–0.62 of the second section blasthole length. Applying the novel proposed procedure for a cut-cavity formation will increase the blasthole use coefficient and reduce the cost of drilling and blasting operations. Moreover, the procedure may also be practical for driving underground mine workings and for ore breaking within stopes.